Enrofloxacin pool doxycycline treatment of canine granuloma leproid: case report - Carvalho, Flávia Clare Goulart; Rosas, Tábata Massessine; Machado, Marília Alves; Lopes, Natalia Lores; Loures, Fabricia Hallack; Conceição, Lissandro Gonçalves; Fernandes, Julio Israel (Brazilian Journal of Veterinary Medicine, 2018)
It is reported a case of canine leproid granuloma in a Boxer at South Fluminense region, in Rio de Janeiro State. Clinical signs included nodular ulcerated lesions, alopecia, and serosanguinous exudate with no complaint of pain or pruritus. The diagnosis was based on the cytopathological and histopathological examination, which revealed intense pyogranulomatous inflammation along with negative bacilli images or acid-fast bacilli, respectively. The treatment protocol was established with enrofloxacin 10 mg/kg once a day associated with doxycycline 10mg / kg once a day for 3 months with clinical cure without recurrence, and no side effects.